2007
DOI: 10.1124/dmd.107.015768
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxybuspirone Is a Major Active Metabolite of Buspirone: Assessment of Pharmacokinetics and 5-Hydroxytryptamine1AReceptor Occupancy in Rats

Abstract: ABSTRACT:The pharmacokinetics and in vivo potency of 6-hydroxybuspirone (6-OH-buspirone), a major metabolite of buspirone, were investigated. The plasma clearance (47.3 ؎ 3.5 ml/min/kg), volume of distribution (2.6 ؎ 0.3 l/kg), and half-life (1.2 ؎ 0.2 h) of 6-OHbuspirone in rats were similar to those for buspirone. Bioavailability was higher for 6-OH-buspirone (19%) compared with that for buspirone (1.4%). After intravenous infusions to steady-state levels in plasma, 6-OH-buspirone and buspirone increased 5-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…9). However, in a clinical pharmacokinetic study, it was shown that 6-hydroxybuspirone is present at much greater concentrations than buspirone and may contribute to activity (Dockens et al, 2006;Wong et al, 2007). If it is assumed that the free fraction of this metabolite is equivalent to buspirone itself, then it can be estimated that the metabolite contributes seven times the activity of the parent.…”
Section: A Drugs With Active Metabolites That Dominate the Activitymentioning
confidence: 99%
“…9). However, in a clinical pharmacokinetic study, it was shown that 6-hydroxybuspirone is present at much greater concentrations than buspirone and may contribute to activity (Dockens et al, 2006;Wong et al, 2007). If it is assumed that the free fraction of this metabolite is equivalent to buspirone itself, then it can be estimated that the metabolite contributes seven times the activity of the parent.…”
Section: A Drugs With Active Metabolites That Dominate the Activitymentioning
confidence: 99%
“…Buspirone (Buspar), used clinically as an anxiolytic, is a serotonin (5-HT) 1A receptor partial agonist and antagonist at D 2 , D 3 , and D 4 receptors (Kula et al, 1994;Tallman et al, 1997;Wong et al, 2007;Bergman et al, 2013). Its relatively high affinity at D 3 and D 4 receptors (98 and 29 nM, respectively; Bergman et al, 2013) and modest selectivity (5-and 16-fold, respectively;Bergman et al, 2013) versus D 2 receptors has focused attention on its use as a potential medication for cocaine abuse (Winhusen et al, 2012(Winhusen et al, , 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Buspirone is an anxiolytic psychotropic drug primarily used to treat generalized anxi ety disorder. 24) It is a selective 5-HT 1A partial agonist, 25,26) and acts as an antagonist at the dopamine D 3 receptors and D 4 receptors. 27) We tried buspirone in one subject and found it was highly effective.…”
Section: Discussionmentioning
confidence: 99%